Pengaruh Model Pembelajaran TGT Berbantu Media Wordwall terhadap Kemampuan Berpikir Kritis Siswa - Ainurrohmah, Indah; Siswono, Tatag Yuli Eko; Wiryanto, Wiryanto (Ideas Publishing, 2024)
Students weak ability to convert ordinary fractions to decimal fractions, as well as difficulties in carrying out multiplication and division of decimal numbers, result in students low critical thinking abilities. This research aims to explain the influence of the TGT learning model assisted by Wordwall media on students critical thinking abilities in fourth grade mathematics subjects at Zainuddun Unggulan Elementary School. This type of research is a pre-experimental one group pretest posttest design. Based on the paired sample t test, a Sig(2-tailed) value of 0.00<0.05 was achieved, so it can be concluded that there is an influence of the TGT learning model assisted by Wordwall media on students critical thinking abilities in fourth grade mathematics subjects at Zainuddun Unggulan Elementary School